Dietary Iron Intake and Serum Ferritin Concentration in 213 Patients Homozygous for the HFEC282Y Hemochromatosis Mutation - Victor R Gordeuk; Laura Lovato; James C Barton; Mara Vitolins; Gordon McLaren; Ronald T Acton; Christine McLaren; Emily L Harris; Mark Speechley; John H Eckfeldt; Sharmin Diaz; Phyliss Sholinsky; et al. (Canadian Journal of Gastroenterology, 2012)
BACKGROUND: HFEC282Y homozygotes have an increased risk for developing increased iron stores and related disorders. It is controversial whether dietary iron restrictions should be recommended to such individuals.